Por que os professores permanecem na profissão? Trajetórias de professores do ensino fundamental da rede municipal de São Paulo - Pereira, Simone dos Santos (2017)
Researchers have pointed out a large number of teachers who exonerate their positions and give up their profession; others reflect on the low numbers of new entries in the teaching career. Among such teaching evasion in Brazilian public schools, we ask, in this work, why does the teacher perpetuate in the profession? The current research aims at understanding the constituent elements of admission and career continuation, albeit with all the adversities faced by the "educational crisis". In this sense, considering the assumptions in the historical-cultural perspective, we aim to unveil and to analyze evidences of the subject's constitution throughout their lifes trajectory, seeking to know their education history and the relations established in different environments, with others and with themselves. The research was carried out on two teachers of the educational system of the city of São Paulo, through semi-structured interviews, with Oral History contributions. Focusing on the entry and permanence in the teaching career our analyses indicate that these teachers remain in the profession: i. For the passion for the discipline taught; ii. So that students would perceive themselves as historical, geographic and social beings; iii. For their political engagement, in which the profession is consistent with the process of transformation they desire for the nation; iv. (Re)significations of the relationships established in school; v. For the career stability in the public sector, among other elements. It was also noticed that, in addition to the elements that facilitated the permanence, it was highlighted the way in which they remained drama between the dreams and the stones, between the intended and the realized, between the personal and the social, between the ideal and the concrete.